Polycyclic aromatic hydrocarbons and volatile organic compounds in biochar and biochar‐amended soil: a review. Issue 6 (26th April 2016) - Dutta, Tanushree; Kwon, Eilhann; Bhattacharya, Satya Sundar; Jeon, Byong Hun; Deep, Akash; Uchimiya, Minori; Kim, Ki‐Hyun
Abstract: Residual pollutants including polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs), and carbon (aceous) nanoparticles are inevitably generated during the pyrolysis of waste biomass and remain on the solid coproduct called biochar. Such pollutants could have adverse effects on the plant growth as well as microbial community in soil. Although biochar has been proposed as a 'carbon negative strategy' to mitigate the greenhouse gas emissions, the impacts of its application with respect to long‐term persistence and bioavailability of hazardous components are not clear. Moreover, the co‐occurrence of low molecular weight VOCs with PAHs in biochar may exert further phytotoxic effects. This review describes the basic need to unravel key mechanisms driving the storage vs. emission of these organics and the dynamics between the sorbent (biochar) and soil microbes. Moreover, there is an urgent need for standardized methods for quantitative analysis of PAHs and VOCs in biochar under environmentally relevant conditions. This review is also extended to cover current research gaps including the influence of biochar application on the short‐ and long‐term fate of PAHs and VOCs and the proper control tactics for biochar quality and associated risk.